Feeding practices of low birth weight Brazilian infants and associated factors - Naiá Ortelan; Daniela Almeida Neri; Maria Helena D'Aquino Benicio (Universidade de São Paulo, 2020)
ABSTRACT OBJECTIVE To characterize complementary feeding and to analyze the influence of individual and contextual factors on dietary practices of low birth weight infants. METHODS This cross-sectional study included 2,370 low birth weight infants aged 6 to 12 months included in the Breastfeeding Prevalence Survey in Brazilian Municipalities (2008), which covered the 26 state capitals, the Federal District and 37 municipalities. Dietary practices were assessed using two indicators: I) dietary diversity, characterized by the consumption of five food groups: meat, beans, vegetables, fruit and milk; II) consumption of ultra-processed foods, characterized by the ingestion of at least one of the following foods on the day prior to the survey: soda, or processed juice, or cookie, cracker and crisps. The covariates of interest were the socioeconomic characteristics of infants, mothers and health services. The contextual factor was the "municipal prevalence of child undernutrition." The individualized effect of the study factors on outcomes was assessed by multilevel Poisson regression. RESULTS Approximately 59% of infants consumed ultra-processed foods, while 29% had diverse feeding. Mothers living in municipalities with child undernutrition prevalence below 10%, with higher education and working outside the home were more likely to offer dietary diversity. Consumption of ultra-processed foods was higher among infants living in municipalities with child undernutrition prevalence below 10%, whose mothers were younger and multiparous. CONCLUSIONS The low prevalence of diverse feeding combined with the high prevalence of ultra-processed food consumption characterizes the low quality of feeding of low birth weight Brazilian infants. Individual and contextual factors impact the feeding quality of this population, suggesting the need for effective strategies to increase the consumption of fresh and minimally processed foods and decrease the consumption of ultra-processed foods by this vulnerable population.